Enhancing OCB through spiritual leadership, workplace spirituality, and Islamic work ethics - Pertiwi, Tanza Dona; Ronny, Ronny; Ratnasari, Ririn Tri; Osman, Ismah; Cholil, Muhammad (Faculty of Business & Economics, Universitas Islam Indonesia, 2025)
Purpose – This study examined the influence of spiritual leadership (SL), workplace spirituality (WS), and Islamic work ethics (IWE) on organizational citizenship behavior (OCB) among employees. It also investigates whether there are generational differences in the effects between Generation Y and Generation Z in Surabaya.Methodology – This research employed a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) and Partial Least Squares Multi-Group Analysis (PLS-MGA) with the aid of SmartPLS 4. The study involved 110 employees from Generation Y and Generation Z who lived and worked in Surabaya.Findings – The results show that spiritual leadership, workplace spirituality, and IWE have a positive and significant impact on OCB. However, the MGA revealed no significant differences between Generation Y and Z in terms of how these variables affected OCB. These findings support Social Exchange Theory, suggesting that when employees feel valued and spiritually supported, they tend to reciprocate with positive behaviors such as OCB. Despite the assumptions in generational theory, both generations respond similarly to spiritually rooted leadership and ethical Islamic values.Implications – This study offers practical insights for organizations with multigenerational workforces to adopt spiritual leadership, foster spiritual workplaces, and apply Islamic work ethics to consistently enhance OCB across generations.Originality – By incorporating multi-group analysis, this research adds to the limited literature on spirituality and ethics in shaping OCB, particularly among Generation Y and Z Muslim employees in a modern workplace setting.